Actin remodelling of the endothelium during transendothelial migration of leukocytes. (December 2020) - van Steen, Abraham C.I.; van der Meer, Werner J.; Hoefer, Imo E.; van Buul, Jaap D.
Abstract: For leukocytes crossing the vessel wall to solve inflammation, the endothelium acts as customs control. In the past years, progress has been made on the molecular mechanisms that are used by both the leukocytes and endothelium to allow efficient crossing, although not all the exact rules these vascular customs play by are completely understood. In this review, we focus on the contribution of the endothelium to the process of leukocyte extravasation and summarize the different molecular mechanisms involved in efficient leukocyte passage and prevention of local leakage at the same time. We will highlight the dynamic regulation of the endothelial actin cytoskeleton, which under the influence of different stimuli is a key player in leukocyte transendothelial migration. Graphical abstract: Image 1 Highlights: This review summarizes the latest findings on leukocyte transendothelial migration, focussing on the role of the endothelium. Focus on the dynamics of the endothelial actin cytoskeleton and how cytoskeletal-based structures support leukocyte passage. This review gives a comprehensive overview of trans- versus paracellular transendothelial migration in literature.